Traditional Cultural Game-Based Group Guidance Model: Efforts to Reduce Introverted Behavior - Namma, Nasia; Aztrid Fithrayani; Andi Muh. Ramadhan AS; Siti Rahmi (ILIN Education Indonesia, 2024)
The purpose of this research is to determine: (1) the design of a traditional game-based group guidance model aimed at reducing introverted behavior among students at SMPN 3 Pangkajene; (2) the validity and practicality of the traditional game-based group guidance model in reducing introverted behavior among students; and (3) the effectiveness of the traditional game-based group guidance model in reducing introverted behavior among students at SMPN 3 Pangkajene. This study is a research and development (R&D) project based on the Borg and Gall method. The expert subjects consist of three professionals: two from academia and one practitioner. The development stages include: (1) information gathering, (2) planning the development of the guidance manual, (3) initial manual development, (4) expert validation, (5) revision of the initial manual, and (6) small group testing. Data collection techniques include questionnaires, interviews, and observations, with a sample size of 15 ninth-grade students exhibiting introverted behavior. The data analysis technique used to test the hypothesis is the Wilcoxon Signed Ranks Test. The research results indicate that: (1) the design of the traditional game-based group guidance model consists of a guidance manual that includes general objectives, targets, and materials covering responsibility, honesty, cooperation, solidarity, leadership, social interaction, empathy, and mutual assistance, as found in the traditional games of massantok, massalo, ma’boy, and songko-songko jangang, along with assessment worksheets to evaluate student understanding; (2) the traditional game-based group guidance model has been tested for validity and practicality, meeting the criteria of accuracy, feasibility, and usability; and (3) group guidance services using traditional games have proven effective in reducing introverted behavior among students, with a noticeable decrease in indicators from a high category before the model was implemented.